The impact of recurrent information on the objectivity of estimation of students’ and teachers’ work - Staniūnienė , G. (Psichologija, 1973)
Objective estimation of the work has a great importance for the development of the training process and for education too. It develops such qualities as right attitude to work, discipline, honesty, care, thoughtfulness, confidence in one’s own abilities, desire to acquire more knowledge, etc. It is shown that by recording recurrent information it is possible to estimate objectively graphic works of student during a semester taking into account the qualities mentioned above (the research was carried out at the Electrical Engineering Faculty of the Kaunas Polytechnic Institute). Quantitative and qualitative abilities and skills are named. It is shown also how to estimate objectively the work of each student while estimating the work by marks. Recurrent information has an impact not only on the objectivity of estimation of student’s work but on that of a teacher as well. Defects in student’s and teacher’s work during semester may be seen in the presented example - summary table. The causes bringing about these defects and means for their elimination are indicated.